Primary Tumor Sidedness Predicts Bevacizumab Benefit in Metastatic Colorectal Cancer Patients - Xia-Hong You; Can Wen; Zi-Jin Xia; Fan Sun; Yao Li; Wei Wang; Zhou Fang; Qing-Gen Chen; Lei Zhang; Yu-Huang Jiang; Xiao-Zhong Wang; Hou-Qun Ying; et al. (Frontiers in Oncology, 2019)
The emerging debate between primary tumor location and clinical outcome of bevacizumab treated metastatic colorectal cancer (mCRC) continues. The aim of the present study is to investigate the association between the primary tumor location and clinical outcome of 115 mCRC patients receiving bevacizumab based treatment. A meta-analysis including 21 studies was carried out to confirm the conclusion. In our prospective study, we found that right-sided mCRC commonly occurred in older cases (p = 0.03) with multiple-site metastasis (p = 0.03). Progression-free survival (PFS) of the left-sided patients undergoing bevacizumab plus a FOLFIRI regimen was superior to the right-sided cases (p = 0.03, crude HR = 0.31, 95%CI = 0.11–0.87; adjusted HR = 0.21, 95%CI = 0.06–0.66). The meta-analysis confirmed that efficacy of bevacizumab-based treatment in left-sided mCRC patients was better than the right-sided cases in the overall population (Ph = 0.24, combined OR = 1.36, 95%CI = 1.07–1.72), RAS/BRAF wild-type (Ph = 0.19, combined OR = 1.66, 95%CI = 1.17–2.34), clinical trial (Ph = 0.23, combined OR = 1.42, 95%CI = 1.07–1.88), Caucasian population (Ph = 0.18, combined OR = 1.37, 95%CI = 1.02–1.85) and first-line (Ph = 0.19, combined OR = 1.48, 95%CI = 1.13–1.96) subgroups. Improved survival of bevacizumab plus chemotherapy treated left-sided mCRC patients was observed in the overall population [Ph < 0.01, combined MSR = 1.09, 95%CI = 1.00–1.18 for PFS; Ph < 0.01, combined MSR = 1.24, 95%CI = 1.13–1.36 for overall survival (OS)], especially in the RAS/BRAF wild-type (Ph = 0.09, combined MSR = 1.10, 95%CI = 1.03–1.19 for PFS; Ph = 0.02, combined MSR = 1.34, 95%CI = 1.21–1.49 for OS). These findings indicate that primary tumor sidedness can predict clinical outcome of bevacizumab-treated RAS/BRAF wild-type mCRC patients and the left-sided patients may benefit more from bevacizumab plus FOLFIRI.